Mengefektifkan Gaya Belajar Auditory melalui Bimbingan Kelompok pada Siswa Kelas XI IPA II dI SMA - Kapandra, Hendri; Sofah, Rahmi; Karim, Kelanawaty (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2014)
Abstract: This study aims to streamline the auditory learning styles of students through the guidance of the group discussion method. This research method uses PTBK the 8 study subjects, obtained from the analysis of questionnaires that have been tested for validity and reliability as well as supporting the observation made. Data were analyzed by descriptive quantitative. The results of this action researchs uggests that groups can make effective guidance auditory learning styles of students in schools. Average scores improved the effectiveness of auditory learning styles of students prior to the action that is 45.5 in the low category. After the first cycle of the action performed on the score to 53.6 are categorized as low to medium. In the second cycle, appeared to score the effectiveness of auditory learning styles increased to 76.1 in the high category. Thus it can be recommended that the guidance of the group can be used to streamline the auditory learning styles of students in schools .